High tap density polycrystalline manganese sesquioxide and method of making same
Patent Information
- Application Number
- CN202610587729.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-04-29
AI Technical Summary
[0004]然而,上述常规制备工艺在实际应用和规模化生产中均存在不同程度的局限性
[0019]在此基础上,通过引入二氧化锰与有机酸水溶液,并经凝胶化处理,利用凝胶网络将二氧化锰颗粒均匀地固定在多孔锰氧化物骨架的孔隙内部及表面。有机酸在凝胶化过程中能够促进不同锰源之间的紧密接触与均匀分散,避免了物理混合不均导致的相分离。在随后的二次煅烧过程中,填充在孔隙中的二氧化锰与骨架发生原位固相反应与结合,不仅消除了内部空隙,还加强了颗粒间的连接强度,从而实现了材料微观结构的致密化修复,最终获得具有高振实密度的多晶三氧化二锰材料。
Smart Images

Figure CN122212254B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polycrystalline manganese trioxide synthesis technology, and more specifically, to a high tap density polycrystalline manganese trioxide and its preparation method. Background Technology
[0002] Manganese trioxide, as an important transition metal oxide, occupies a significant position in energy storage, environmental catalysis, and electronic devices due to its abundant oxidation states, low raw material costs, and environmental friendliness. In particular, thanks to its unique electrochemical and magnetic properties, manganese trioxide is often used as a key precursor in the preparation of lithium-ion battery cathode materials (such as lithium manganese oxide), and its physicochemical properties directly affect the performance of the final battery material.
[0003] Currently, the main industrial methods for preparing manganese trioxide powder include liquid-phase and solid-phase methods. Common specific processes include hydrothermal / solvothermal methods, co-precipitation methods, sol-gel methods, and thermal decomposition methods. These methods can prepare the target product in laboratory research or specific scenarios and are the main approaches to obtaining manganese oxide materials in existing technologies.
[0004] However, the aforementioned conventional preparation processes all have limitations to varying degrees in practical applications and large-scale production. For example, hydrothermal or solvothermal methods typically have long reaction cycles and limited single-batch yields, making it difficult to achieve continuous large-scale production; while coprecipitation methods offer considerable yields, particle agglomeration during the preparation process leads to poor particle size distribution uniformity in the product; although sol-gel methods can better control the stoichiometry, their process flow is relatively complex, with long production cycles and high costs; and while thermal decomposition methods are simple and produce products with high crystallinity, they often require long-term processing at high temperatures, resulting in high energy consumption.
[0005] More importantly, the manganese trioxide materials prepared using the aforementioned existing technologies often fail to meet the high standards required for high-performance batteries in terms of microstructure and physical properties. A common problem is the relatively loose particle size, resulting in low tap density. Furthermore, the electrical conductivity of ordinary manganese trioxide is also limited. These defects of low tap density and low conductivity directly restrict its application potential as a precursor in the synthesis of high-performance, high-volume-energy-density battery cathode materials, making it difficult to meet the increasingly stringent performance demands of the current market for battery-grade materials.
[0006] In view of this, the present invention is hereby proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a high tap density polycrystalline manganese trioxide and its preparation method. The preparation method utilizes polymer microspheres to construct a porous framework, and through gelation, manganese dioxide is uniformly filled into the pores of the framework. After secondary calcination, in-situ reaction and densification between components are achieved, effectively eliminating internal voids and significantly improving the tap density of manganese trioxide.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing high-tap-density polycrystalline manganese trioxide, comprising: Manganese tetroxide is mixed with polymer microspheres and subjected to a first calcination treatment to obtain porous polycrystalline manganese oxide; wherein, the manganese oxide includes a composite of manganese trioxide and manganese tetroxide; The porous polycrystalline manganese oxide and manganese dioxide are mixed with an aqueous organic acid solution and then gelled to obtain a gel product. The gel product is then subjected to a second calcination treatment to obtain the high tap density polycrystalline manganese trioxide.
[0009] In an optional embodiment, the temperature of the first calcination treatment is 400°C to 600°C; and / or, The first calcination treatment lasts for 2 to 12 hours; and / or, The second calcination treatment is performed at a temperature of 600℃ to 800℃; and / or, The second calcination treatment lasts for 2 to 12 hours; and / or, The organic acid includes at least one selected from citric acid, oxalic acid, and tartaric acid; and / or, The gelation process includes heating the mixture under stirring until a gel is formed.
[0010] In an optional embodiment, the D50 particle size of the manganese tetroxide is 7 micrometers to 12 micrometers; and / or, The polymer microspheres have a D50 particle size of 100 nm to 200 nm; and / or, The manganese dioxide has a D50 particle size of 100 nm to 200 nm; and / or, The polymer microspheres include at least one of polystyrene microspheres and polymethyl methacrylate microspheres; and / or, The mass of the polymer microspheres is 5% to 20% of the total mass of the manganese tetroxide.
[0011] In an optional embodiment, the step of mixing manganese tetroxide with polymer microspheres further includes adding a metal dopant; wherein the mass of the metal element in the metal dopant is 0.1% to 2% of the total mass of the manganese tetroxide; and / or, The mass ratio of the porous polycrystalline manganese oxide to manganese dioxide is (6-8):(4-2); and / or, The porous polycrystalline manganese oxide has a porosity of 20%–40%, and the proportion of manganese trioxide phase is greater than 60%; and / or, The high-tap-density polycrystalline manganese trioxide has a tap density greater than 2.5 g / cm³. 3 .
[0012] Secondly, the present invention provides a high tap density polycrystalline manganese trioxide, which is prepared by the preparation method of high tap density polycrystalline manganese trioxide as described in any of the foregoing embodiments.
[0013] Thirdly, the present invention provides a lithium manganese oxide cathode material, which is prepared by reacting high tap density polycrystalline manganese trioxide with a lithium source as described in the foregoing embodiments.
[0014] In an optional embodiment, the discharge capacity of the lithium manganese oxide cathode material is greater than 120 mAh / g.
[0015] Fourthly, the present invention provides a method for preparing the lithium manganese oxide cathode material as described in the foregoing embodiments, comprising: The high tap density polycrystalline manganese trioxide as described in the aforementioned embodiments is mixed with a lithium source and subjected to a third calcination treatment at a temperature of 600℃~800℃ to prepare a lithium manganese oxide cathode material.
[0016] Fifthly, the present invention provides a battery comprising a lithium manganese oxide cathode material as described in the foregoing embodiments; or a lithium manganese oxide cathode material prepared by the preparation method described in the foregoing embodiments.
[0017] In a sixth aspect, the present invention provides an electrical device including a battery as described in the foregoing embodiments.
[0018] This invention provides a high-tap-density polycrystalline manganese trioxide and its preparation method. The preparation method employs a strategy combining pore-forming and filling, significantly improving the tap density of the product. By mixing manganese trioxide with polymer microspheres and calcining them, a porous polycrystalline manganese oxide framework is constructed during the partial conversion of manganese trioxide to manganese trioxide through the decomposition of the polymer microspheres at high temperature. This porous structure not only preserves the macroscopic morphology of the precursor but also provides abundant internal space and structural sites for subsequent densification and filling, overcoming the problems of particle agglomeration or excessive looseness in traditional methods.
[0019] Building upon this foundation, by introducing manganese dioxide and an aqueous solution of organic acid, followed by gelation treatment, manganese dioxide particles are uniformly fixed within and on the surface of the porous manganese oxide framework using a gel network. During gelation, the organic acid promotes close contact and uniform dispersion between different manganese sources, preventing phase separation caused by uneven physical mixing. In the subsequent secondary calcination process, the manganese dioxide filling the pores undergoes an in-situ solid-phase reaction and bonding with the framework, eliminating internal voids and strengthening the interparticle connections. This achieves densification and repair of the material's microstructure, ultimately yielding a polycrystalline manganese trioxide material with high tap density. Attached Figure Description
[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 This is a schematic flowchart of the method for preparing high tap density polycrystalline manganese trioxide in an embodiment of the present invention; Figure 2 The image shows the XRD pattern of the porous polycrystalline manganese oxide intermediate in Example 1 of this invention. Figure 3 This is a scanning electron microscope image of the porous polycrystalline manganese oxide intermediate in Example 1 of the present invention; Figure 4 The image shown is the XRD pattern of polycrystalline manganese trioxide in Example 1 of this invention. Figure 5 This is a scanning electron microscope image of polycrystalline manganese trioxide in Example 1 of the present invention. Detailed Implementation
[0022] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0023] refer to Figure 1 This application provides a method for preparing high-tap-density polycrystalline manganese trioxide, comprising: Step S1: Manganese tetroxide is mixed with polymer microspheres and subjected to a first calcination treatment to obtain porous polycrystalline manganese oxide; wherein the manganese oxide includes a composite of manganese trioxide and manganese tetroxide.
[0024] The above-mentioned mixing refers to the physical mixing of manganese tetroxide (Mn3O4) powder, which serves as a manganese source precursor, and polymer microspheres, which serve as pore-forming agents, so that the microspheres are uniformly dispersed between the manganese source particles.
[0025] The first calcination treatment mentioned above refers to heating the mixture at high temperature. During this process, two key changes occur: first, the polymer microspheres decompose, burn, or vaporize due to the high temperature, leaving pores in their original positions; second, manganese tetroxide undergoes a partial oxidation reaction with oxygen in the air at high temperature to generate manganese trioxide (Mn2O3).
[0026] This step yields an intermediate material, namely "porous polycrystalline manganese oxide". This intermediate exhibits a porous structure in its macroscopic morphology (generated by the decomposition of microspheres). Chemically, it is a "complex," meaning it is not completely converted to manganese trioxide, but retains some unreacted manganese tetroxide, exhibiting a two-phase coexistence state.
[0027] The treatment method in this step constructs a skeletal structure with containment capacity, providing physical space for subsequent filling with high-density materials. Compared to direct reaction, this pretreatment method achieves preliminary crystal transformation and structural rearrangement.
[0028] Specifically, mixing can be performed using conventional powder mixing methods such as ball milling and stirring. Calcination is usually carried out in a furnace with an oxygen-containing atmosphere (such as air).
[0029] Step S2: The porous polycrystalline manganese oxide and manganese dioxide are mixed with an organic acid aqueous solution and gelled to obtain a gel product. The gel product is then subjected to a second calcination treatment to obtain the high tap density polycrystalline manganese trioxide.
[0030] In this step, the porous framework prepared in step S1 is added together with manganese dioxide (MnO2, usually used as filler particles) into an aqueous solution of organic acid.
[0031] The gelation process described above is crucial in this step. It involves increasing the viscosity of the liquid system through heating, stirring, or pH adjustment, ultimately forming a gel with a three-dimensional network structure. Here, the organic acid not only acts as a dispersion medium, but its functional groups (such as carboxyl groups) can also complex or coordinate with manganese ions.
[0032] The aforementioned gel product is formed by tightly wrapping and fixing the porous framework and manganese dioxide particles in a gel network, so as to prevent the particles from settling or separating in subsequent processing and ensure that manganese dioxide can be effectively retained inside or on the surface of the porous framework.
[0033] The second calcination treatment mentioned above is a high-temperature sintering process for the gel.
[0034] This step decomposes and eliminates organic matter (gel components and organic acids). Manganese dioxide decomposes at high temperature, releasing oxygen and being reduced to manganese trioxide. The manganese tetroxide remaining in step S1 is further oxidized at high temperature, also transforming into manganese trioxide. The final product is a high-purity, uniformly crystallized polycrystalline manganese trioxide with high tap density.
[0035] In this step, small manganese dioxide particles fill the pores of the large particle skeleton and fuse with the skeleton through in-situ chemical reaction, significantly reducing the voids inside the particles and greatly improving the tap density of the material; the gelation treatment ensures the uniformity of the filler distribution and avoids component segregation caused by simple physical mixing; the complexation effect of organic acids helps to form stronger chemical connections between particles during calcination, rather than loose physical contact, which is conducive to the formation of a continuous conductive network.
[0036] The aforementioned gelation can be achieved by heating the mixture under stirring conditions, promoting solvent evaporation and solute cross-linking until a non-flowing gel-like substance is formed. The organic acid can be an acid capable of coordinating with metal ions, such as citric acid or oxalic acid. The aforementioned calcination can be performed within the suitable temperature range for the phase transition of manganese oxides.
[0037] This embodiment employs a "pore-filling-in-situ composite" strategy. First, a porous manganese oxide framework is constructed by decomposing polymer microspheres during the first calcination, providing space for subsequent densification. Second, small-diameter manganese dioxide particles are uniformly fixed within the framework pores through the complexation and gelation effects of organic acids, forming a stable network structure. Finally, a second calcination initiates an in-situ solid-state reaction, causing manganese dioxide to release oxygen and transform into manganese trioxide, while simultaneously oxidizing the residual manganese tetroxide in the framework, achieving chemical bonding and crystal phase unification of multiple components. This method effectively overcomes the defects of loose manganese trioxide particles and low tap density in existing technologies. Through the dual effects of physical filling and chemical reaction, internal voids within the particles are significantly eliminated, constructing a dense, continuous three-dimensional interpenetrating structure, thereby greatly improving the material's tap density and conductivity, and obtaining high-purity, high-quality polycrystalline manganese trioxide with a uniform microstructure.
[0038] In some embodiments, the temperature of the first calcination treatment is 400°C to 600°C. For example, it can be 400°C, 425°C, 450°C, 480°C, 500°C, 520°C, 550°C, 575°C, 600°C, etc.
[0039] In some embodiments, the first calcination treatment time is 2 to 12 hours. For example, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 9 hours, 10 hours, 12 hours, etc.
[0040] In this method, the mixture can be placed in a heating device, and the temperature controlled between 400°C and 600°C for 2 to 12 hours. Under these conditions, the polymer microspheres undergo thermal decomposition or combustion, and manganese tetroxide undergoes a partial oxidation reaction. This temperature range is sufficient to allow the polymer microspheres to completely decompose and create pores, while avoiding excessively high temperatures that could lead to severe sintering and shrinkage of the framework, thus sealing the pores. The time range ensures the thoroughness of the pore-forming process and the stability of the crystal phase transformation (to manganese trioxide).
[0041] In some embodiments, the temperature of the second calcination treatment is 600°C to 800°C. For example, it can be 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, etc.
[0042] In some embodiments, the second calcination treatment time is 2 to 12 hours. For example, it can be 2 hours, 3.5 hours, 4 hours, 6 hours, 7.5 hours, 8 hours, 10 hours, 11 hours, 12 hours, etc.
[0043] In this step, the gel product is heated at 600°C to 800°C for 2 to 12 hours. During this process, the organic components of the gel decompose, the manganese dioxide filling releases oxygen and transforms into manganese trioxide, and the incompletely reacted framework also transforms into manganese trioxide. This temperature is slightly higher than the first calcination temperature, which helps to promote in-situ solid-phase reactions and enhance the bonding force between particles. This temperature range is conducive to the formation of pure-phase manganese trioxide and promotes moderate grain growth to improve density.
[0044] In some embodiments, the organic acid includes at least one of citric acid, oxalic acid, and tartaric acid.
[0045] In the preparation process, one or more of the above-mentioned acids are used to prepare aqueous solutions. These acids have abundant carboxyl functional groups. These organic acids can undergo strong coordination or chelation with manganese ions to form stable metal-organic complexes. During gelation, this coordination helps to strengthen the microscopic connection between manganese dioxide and the framework, preventing phase separation.
[0046] In some embodiments, the gelation process includes heating the mixture under stirring conditions until a gel is formed.
[0047] This step involves mixing the porous framework, manganese dioxide, and organic acid solution, followed by mechanical stirring and heating until the mixture loses its fluidity and transforms into a gel state.
[0048] Gelation treatment prevents the solid particles (porous framework and manganese dioxide) from settling before gelation, ensuring that the filler is evenly distributed around the framework and in the pores. It also accelerates solvent evaporation and cross-linking reactions between solutes, shortening process time and improving production efficiency.
[0049] In some embodiments, the D50 particle size of the manganese tetroxide is 7 micrometers to 12 micrometers. For example, it can be 7 micrometers, 7.5 micrometers, 8 micrometers, 9 micrometers, 10 micrometers, 10.5 micrometers, 11 micrometers, 11.5 micrometers, 12 micrometers, etc.
[0050] As a supporting framework, larger micron-sized particles (7~12μm) can provide a stable macroscopic structural foundation, preventing excessive collapse during subsequent high-temperature processing.
[0051] In some embodiments, the D50 particle size of the polymer microspheres is 100 nm to 200 nm. For example, it can be 100 nm, 110 nm, 120 nm, 130 nm, 150 nm, 160 nm, 180 nm, 190 nm, 200 nm, etc.
[0052] Since the microspheres decompose and disappear at high temperatures, their particle size directly determines the size of the pores left in the framework (i.e., the pore size is approximately 100-200 nm). Nanoscale pores are created specifically to accommodate subsequently added nanoscale fillers.
[0053] In some embodiments, the D50 particle size of the manganese dioxide is 100 nm to 200 nm. For example, it can be 100 nm, 115 nm, 125 nm, 140 nm, 150 nm, 165 nm, 175 nm, 185 nm, 200 nm, etc.
[0054] This particle size range (100-200nm) can be highly matched with the pore size (100-200nm) created by polymer microspheres, ensuring that manganese dioxide particles can be smoothly embedded in the pores of the porous framework, achieving a tight filling of "pore-particle matching" and thus maximizing the tap density.
[0055] In some embodiments, the polymer microspheres include at least one of polystyrene microspheres and polymethyl methacrylate microspheres.
[0056] Both polymers mentioned above have clean combustion properties and can completely decompose into gas at calcination temperature, leaving no carbon or other impurities in the product, thus ensuring the high purity of manganese trioxide.
[0057] In some embodiments, the mass of the polymer microspheres is 5% to 20% of the total mass of manganese tetroxide. For example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, etc.
[0058] The lower limit of 5% ensures that enough pores are generated, avoiding insufficient filling due to low porosity; the upper limit of 20% prevents excessive pores from causing the skeleton structure to become fragile or collapse, thus maintaining the mechanical stability of the skeleton.
[0059] In some embodiments, the step of mixing manganese tetroxide with polymer microspheres further includes adding a metal dopant; wherein the mass of the metal element in the metal dopant is 0.1% to 2% of the total mass of manganese tetroxide. For example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.7%, 1.9%, 2.0%, etc.
[0060] In this step, trace amounts of other metallic elements are introduced during the mixing process. Metal ions enter the crystal lattice of the manganese oxide, forming a doped structure. By introducing heteroatoms, the electronic structure or oxygen vacancy concentration of the material can be modulated, thereby optimizing the electrochemical performance (such as conductivity or reactivity) of the final product without altering its high tap density physical properties.
[0061] In some embodiments, the mass ratio of the porous polycrystalline manganese oxide to manganese dioxide is (6-8):(4-2). The porous polycrystalline manganese oxide can be, for example, 6 parts, 7 parts, 8 parts, etc., based on the weight parts of each component in the ratio; the manganese dioxide can be, for example, 2 parts, 3 parts, 4 parts, etc.
[0062] The above ratio represents the optimized filling ratio. If there is too little manganese dioxide (<2), the pores will not be fully filled, resulting in limited density improvement. If there is too much manganese dioxide (>4), the pores cannot accommodate it, and the excess nanoparticles will accumulate on the outside of the framework, causing agglomeration and reducing the tap density.
[0063] In some embodiments, the porosity of the porous polycrystalline manganese oxide is 20% to 40% (e.g., it can be 20%, 22%, 25%, 28%, 30%, 33%, 35%, 36%, 38%, 40%, etc.), and the proportion of manganese trioxide phase is greater than 60%. For example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, etc.
[0064] The aforementioned porosity of 20%-40% indicates successful pore formation, providing ample space for the second-step filling process. The phase content >60% indicates that most of the manganese tetroxide has undergone oxidation transformation during the first calcination process, achieving the expected crystal form control, which is beneficial for the subsequent formation of a uniform pure-phase structure.
[0065] The high-tap-density polycrystalline manganese trioxide has a tap density greater than 2.5 g / cm³. 3 .
[0066] The powder material prepared by this method has a density exceeding 2.5 g / cm³ after vibration compaction. 3 This value is significantly higher than that of materials prepared by conventional methods, meaning that when used as a precursor for battery cathode materials, it can significantly improve the volumetric energy density of the battery, and has extremely high commercial application value.
[0067] This application also provides a high tap density polycrystalline manganese trioxide, which is prepared by the preparation method of high tap density polycrystalline manganese trioxide as described in any of the foregoing embodiments.
[0068] Because this polycrystalline manganese trioxide undergoes a unique "microsphere pore-forming-nanofilling-gelation in-situ composite" process, it inevitably forms a special structure at the microscopic level that differs from products obtained by conventional precipitation or thermal decomposition methods. This structure is a dense three-dimensional interpenetrating network formed by a micrometer-scale framework and nanoscale fillers tightly bonded together by chemical bonds. This structural feature directly endows the product with excellent physical properties, giving it a high tap density (greater than 2.5 g / cm³). 3 It has significant advantages such as high purity.
[0069] In this embodiment, a lithium manganese oxide cathode material is provided, which is prepared by reacting high tap density polycrystalline manganese trioxide with a lithium source as described in the aforementioned embodiments.
[0070] The aforementioned lithium source is a raw material that provides lithium element, which may include lithium-containing compounds such as lithium carbonate that can react with manganese oxides.
[0071] The aforementioned specific precursor is high-tap-density polycrystalline manganese trioxide, which possesses the special dense structure and high tap-density characteristics formed by "microsphere pore formation and gel filling" as defined above.
[0072] The principle is that, by utilizing the principle of high-temperature solid-state reaction, lithium ions diffuse into the polycrystalline manganese trioxide lattice at high temperature, and undergo a phase transition to generate lithium manganese oxide.
[0073] Since the precursor (manganese trioxide) has already achieved microstructure densification, composition homogenization and valence state unification (pretreatment) through a special "pore-forming-filling-in-situ composite" process, this excellent framework structure is inherited by lithium manganese oxide after reacting with the lithium source.
[0074] In some embodiments, the discharge capacity of the lithium manganese oxide cathode material is greater than 120 mAh / g.
[0075] The above capacity values are the core indicators for measuring the electrochemical performance of cathode materials, representing the amount of charge that can be released per unit mass of material.
[0076] Thanks to the use of a high-tap-density precursor, the synthesized lithium manganese oxide material naturally inherits the high tap density characteristic. Combined with a high capacity greater than 120 mAh / g, it can significantly improve the volumetric energy density of the battery. The precursor has undergone homogenization treatment of the manganese source, avoiding the problem of incomplete reaction caused by uneven mixing of various manganese oxides in traditional processes. This results in a final product with fewer impurities, a complete crystal structure, and fewer lattice defects, thereby achieving high first-cycle efficiency (initial coulombic efficiency) and excellent cycle stability.
[0077] In this embodiment of the application, a method for preparing lithium manganese oxide cathode material as described in the foregoing embodiments is provided, comprising: The high-taper-density polycrystalline manganese trioxide as described in the preceding embodiments is mixed with a lithium source and subjected to a third calcination treatment at a temperature of 600°C to 800°C (for example, 600°C, 625°C, 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, etc.) to prepare a lithium manganese oxide cathode material.
[0078] The above-described mixing process involves physically mixing high-tap-density polycrystalline manganese trioxide with a lithium source at a stoichiometric ratio (e.g., a lithium-to-manganese ratio of approximately 1.095, depending on the specific implementation). Mechanical mixing methods can be used to ensure that lithium source particles are uniformly attached to the surface of manganese source particles. Since the precursor (manganese trioxide) is already a pure-phase material with a single composition and uniform microstructure, this step achieves more uniform mixing and more efficient reaction contact area compared to using complex mixed manganese sources, laying the foundation for consistent subsequent reactions.
[0079] The third calcination treatment described above is a key thermal treatment step in the synthesis of lithium manganese oxide, namely the "lithiation" process. Its temperature can be limited to 600℃~800℃. The process can involve high-temperature heating in an oxygen-containing atmosphere. Within this temperature range, lithium salts decompose (e.g., lithium carbonate decomposes to release carbon dioxide), and lithium ions diffuse and embed into the crystal structure of manganese trioxide. With adjustments to the oxygen content, the crystal structure transforms from a ferromanganese oxide structure to a spinel structure (LiMn2O4), thereby preparing a lithium manganese oxide cathode material with high crystallinity and accurate stoichiometry.
[0080] The temperature range mentioned above is 600℃~800℃, which is the optimal window for the formation of spinel lithium manganese oxide. Too low a temperature will lead to incomplete reaction, residual raw materials, or the formation of impurity phases; too high a temperature may lead to excessive grain growth or oxygen vacancies, affecting electrochemical performance.
[0081] At this temperature, the high tap density of the precursor is maintained, and the particles will not break or collapse due to drastic phase transitions, thus ensuring the high tap density of the final product.
[0082] In this application embodiment, a battery is provided, including the lithium manganese oxide cathode material as described in the foregoing embodiments; or, the lithium manganese oxide cathode material prepared by the preparation method described in the foregoing embodiments.
[0083] The core feature of the aforementioned battery lies in its use of lithium manganese oxide, which possesses high tap density and high capacity, as the positive electrode active material. Structurally, this battery typically includes a positive electrode assembly (containing the aforementioned lithium manganese oxide positive electrode material, a conductive agent, a binder, and a current collector), a negative electrode assembly (containing a negative electrode active material such as graphite or silicon carbon), a separator between the positive and negative electrodes, and an electrolyte (such as a liquid electrolyte or a solid electrolyte). Based on the excellent tap density and electrochemical performance of this positive electrode material, the battery exhibits high volumetric energy density and good cycle stability. Specific types of the battery include, but are not limited to, lithium-ion secondary batteries, lithium polymer batteries, solid-state lithium batteries, and various energy storage devices employing lithium-ion intercalation / deintercalation mechanisms.
[0084] In this application embodiment, an electrical device is provided, including a battery as described in the foregoing embodiments.
[0085] The aforementioned electrical equipment refers to any device, system, or appliance that uses the aforementioned battery as a driving power source, auxiliary power source, or energy storage unit. Because of its high capacity and excellent safety, this battery can provide stable power support for the equipment. The scope of such electrical equipment is very broad, including but not limited to: mobile communication devices (such as smartphones and tablets), portable electronic products (such as laptops and smart wearable devices), electric vehicles (such as electric bicycles, electric cars, and hybrid vehicles), power tools (such as electric drills and chainsaws), energy storage systems (such as home energy storage stations and portable power banks), and other instruments or smart terminals that require mobile power supply.
[0086] The present invention will be further illustrated below with specific embodiments. However, it should be understood that these embodiments are merely for the purpose of more detailed illustration and should not be construed as limiting the present invention in any way.
[0087] Example 1 In this embodiment, a high tap density polycrystalline manganese trioxide and its downstream lithium manganese oxide cathode material are prepared.
[0088] Experimental methods: (1) Construction of porous framework: 1000g of high-purity manganese tetroxide powder with a D50 particle size of 10 micrometers was selected, along with 95g of polystyrene (PS) microspheres with a D50 particle size of 180 nanometers (accounting for 9.5% of the mass of manganese tetroxide) and 28.9g of aluminum hydroxide dopant (equivalent to 10g of metallic aluminum element, accounting for 1%). The above raw materials were mixed evenly in a high-speed mixer. The mixture was placed in a muffle furnace and subjected to a first calcination treatment in an air atmosphere, heated to 500℃ and held for 7 hours. After natural cooling, a porous polycrystalline manganese oxide intermediate was obtained. The porosity of the intermediate was tested to be 29.8%. Figure 2 The XRD pattern of this intermediate shows that its phase composition is a complex of manganese trioxide and manganese tetroxide (manganese trioxide accounts for 80.9%). Figure 3 Here is a surface SEM image of the intermediate.
[0089] (2) Gel filling and in-situ composite: Take 700g of the porous polycrystalline manganese oxide intermediate prepared above, and 300g of manganese dioxide powder with a D50 particle size of 180 nm (mass ratio 7:3). Add both to an aqueous solution containing 200g of citric acid (the amount of citric acid is sufficient to form a stable complex and initiate gelation), and heat in a constant temperature water bath while stirring (temperature about 80℃) until the water evaporates and the mixture loses its fluidity to form a gel product. Place the gel product in a tube furnace for a second calcination treatment, raise the temperature to 700℃, and hold for 7 hours. During the calcination process, the gel decomposes, manganese dioxide releases oxygen and chemically bonds with the framework. After cooling, grind and sieve to obtain high tap density polycrystalline manganese trioxide. Figure 4 The XRD pattern of the product shows complete peak shapes and high crystallinity. Figure 5 The image shows a SEM image of the product surface, revealing a dense structure.
[0090] (3) Preparation of lithium manganese oxide: The high tap density polycrystalline manganese trioxide prepared above was mixed with battery-grade lithium carbonate at a Li / Mn molar ratio of 1.095. The mixture was subjected to a third calcination treatment at 750°C in air atmosphere for 16 hours. After natural cooling, lithium manganese oxide cathode material was obtained.
[0091] Example 2 This embodiment uses basically the same method as Embodiment 1, the only difference being: In step (1), the temperature of the first calcination treatment is set to 400°C and the holding time is 7 hours.
[0092] In step (2), the temperature of the second calcination treatment is set to 600°C and the holding time is 7 hours.
[0093] The specifications and proportions of the remaining raw materials are consistent with those in Example 1.
[0094] Example 3 This embodiment uses basically the same method as Embodiment 1, the only difference being: In step (1), the temperature of the first calcination treatment is set to 600°C and the holding time is 7 hours.
[0095] In step (2), the temperature of the second calcination treatment is set to 800°C and the holding time is 7 hours.
[0096] The specifications and proportions of the remaining raw materials are consistent with those in Example 1.
[0097] Example 4 This embodiment uses basically the same method as Embodiment 1, the only difference being: In step (1), the amount of polystyrene (PS) microspheres added is 5% of the mass of manganese tetroxide.
[0098] The holding time for the first calcination treatment is set to 2 hours.
[0099] The remaining conditions remain the same as in Example 1.
[0100] Example 5 This embodiment uses basically the same method as Embodiment 1, the only difference being: In step (1), the amount of polystyrene (PS) microspheres added is 20% of the mass of manganese tetroxide.
[0101] The holding time for the first calcination treatment was set to 12 hours.
[0102] The remaining conditions remain the same as in Example 1.
[0103] Example 6 This embodiment uses a method that is basically the same as that in Embodiment 1, the only difference being the selection of raw materials: In step (1), the polymer microspheres used are replaced with polymethyl methacrylate (PMMA) microspheres with a D50 particle size of 180 nanometers, and the amount added is still 9.5%.
[0104] The remaining steps and parameters are the same as in Example 1.
[0105] Example 7 This embodiment uses a method that is basically the same as that in Embodiment 1, the only difference being the selection of raw materials: In step (2), the citric acid aqueous solution used is replaced with an oxalic acid aqueous solution.
[0106] The remaining steps and parameters are the same as in Example 1.
[0107] Example 8 This embodiment uses a method that is basically the same as that in embodiment 1, the only difference being the feeding ratio in step (2): The mass ratio of porous polycrystalline manganese oxide intermediate to manganese dioxide powder was adjusted to (6:4), that is, 600g of porous skeleton and 400g of manganese dioxide.
[0108] The remaining steps and parameters are the same as in Example 1.
[0109] Comparative Example 1 This comparative example aims to verify the necessity of "polymer microsphere pore creation".
[0110] The specific steps are as follows: Manganese tetroxide with a D50 of 10 micrometers was mixed with a metal dopant without adding polymer microspheres.
[0111] The first calcination treatment was carried out directly (500℃, 7 hours) to obtain non-porous manganese oxide.
[0112] The non-porous manganese oxide was mixed with nano-manganese dioxide at a ratio of 7:3, citric acid was added to gel the mixture, and a second calcination was carried out (700℃, 7 hours).
[0113] The subsequent preparation steps for lithium manganese oxide are the same as in Example 1.
[0114] Note: Due to the lack of a porous framework, nano-manganese dioxide cannot fill the interior of the particles and can only adhere to the surface or form independent aggregates.
[0115] Comparative Example 2 This comparative example aims to verify the necessity of "manganese dioxide filling and secondary calcination".
[0116] The specific steps are as follows: Step (1) is the same as in Example 1 (normal pore formation).
[0117] The manganese dioxide filling and gelation process in step (2) is omitted. The porous polycrystalline manganese oxide obtained in step (1) is used directly as a precursor.
[0118] The porous precursor was directly mixed with lithium carbonate and subjected to a third calcination to prepare lithium manganese oxide.
[0119] Note: Due to the lack of pore filling, there are a large number of voids inside the precursor, and the expected tap density is low.
[0120] Comparative Example 3 This comparative example aims to verify the particle size matching effect of "micron framework + nanofiller".
[0121] The specific steps are as follows: Step (1) is the same as in Example 1 (the pore size is approximately nanometers).
[0122] In step (2), the manganese dioxide used is replaced with large-particle manganese dioxide with a D50 of 2 micrometers.
[0123] The remaining steps are the same as in Example 1.
[0124] Note: Because the filler particle size is much larger than the pore size of the framework, it cannot enter the interior of the pores and cannot achieve densification. This comparative example does not provide corresponding SEM morphology images, but its tap density, compaction density, and electrochemical performance are significantly inferior to those of the examples, which fully confirms that large-particle manganese dioxide cannot achieve pore filling and structural densification.
[0125] Comparative Example 4 This comparative example aims to verify the necessity of "organic acid gelation and in-situ reaction".
[0126] The specific steps are as follows: Step (1) is the same as in Example 1.
[0127] In step (2), porous polycrystalline manganese oxide and nano-manganese dioxide are directly mixed by dry physical mixing without adding organic acids or undergoing a gelation process.
[0128] The physical mixture was directly subjected to a second calcination (700°C, 7 hours).
[0129] The subsequent preparation steps for lithium manganese oxide are the same as in Example 1.
[0130] Note: Due to the lack of gel network fixation and organic acid complexation, the filling uniformity is poor and the interfacial bonding is weak.
[0131] Test Experiment 1. Testing method: (1) Tap density test method: Test subjects: manganese trioxide precursor powder and lithium manganese oxide cathode material powder in the examples and comparative examples.
[0132] Testing instrument: Dandong Better Vibration Density Tester.
[0133] Test Procedure: Accurately weigh 50g of the powder sample to be tested, denoted as m. Pour all the powder into a clean, dry graduated cylinder. Fix the graduated cylinder onto the tapped density meter. Set the vibration frequency (250 times / min) and vibration amplitude (3mm), and set the number of vibrations to 3000 times until the powder volume no longer changes. Read the volume of the powder after tapping, denoted as V.
[0134] Calculation formula: Tap density = m / V (g / cm³) 3 ).
[0135] (2) Compacted density test method: Test subject: Lithium manganese oxide cathode material powder in the examples and comparative examples.
[0136] Test Procedure (Powder Compression Method): Weigh a certain mass of powder sample (1.0g) and place it into a mold. Apply a pressure of 222 MPa using a hydraulic press and hold the pressure for 1 minute. Remove the compressed sample block, measure its thickness h and diameter d, and calculate the compaction density.
[0137] (3) Discharge capacity and cycle testing methods: Test subject: assembled button cells (half-cells) in the examples and comparative examples.
[0138] Test conditions: Positive electrode: Lithium manganese oxide material prepared in the examples / comparative examples.
[0139] Negative electrode: Lithium metal sheet.
[0140] Electrolyte: Standard lithium hexafluorophosphate (LiPF6) electrolyte.
[0141] Separator: Porous diaphragm of polypropylene (PP) or polyethylene (PE).
[0142] Testing equipment: Battery testing system (Blue Button Battery Testing System).
[0143] Room temperature rate test: The button cell battery was subjected to constant current charge-discharge cycles of 3 times at current densities of 0.1C, 1C, 2C and 5C, with a voltage range of 3~4.3V.
[0144] Room temperature cycle test: The button cell battery was subjected to one constant current charge-discharge cycle at a current density of 0.1C, and then to 100 constant current charge-discharge cycles at a current density of 1C, with a voltage range of 3~4.3V.
[0145] 55℃ high temperature cycle test: The button battery was subjected to one constant current charge-discharge cycle at a current density of 0.1C, and then to 100 constant current charge-discharge cycles at a current density of 1C, with a voltage range of 3~4.3V.
[0146] (4) Particle size distribution (D50) test method: Testing instrument: Malvern laser particle size analyzer (UK).
[0147] Test medium: Deionized water was used as the dispersant, supplemented by ultrasonic dispersion.
[0148] Particle size is measured using the principle of laser scattering. D50 represents the particle size value (i.e., median particle size) when the cumulative volume distribution reaches 50%.
[0149] (5) Porosity testing methods Testing instrument: Gas adsorption analyzer (BET method).
[0150] For nanoscale mesopores, nitrogen adsorption-desorption method (BET / BJH model) is usually used.
[0151] Measure the total pore volume of the material and calculate the porosity based on the material's theoretical density.
[0152] (6) Phase analysis (XRD): Testing instrument: Bruker D6 X-ray powder diffractometer.
[0153] Test parameters: Cu target Kα rays, scanning range (2θ) of 15°~70°, scanning speed of, for example, 5° / min.
[0154] 2. Test Results: Table 1 below lists the tap density of the manganese trioxide precursors prepared in Examples 1-8 and Comparative Examples 1-4, and the tap density and compaction density of the corresponding synthesized lithium manganese oxide cathode materials. Table 2 lists the discharge capacity of the lithium manganese oxide cathode materials prepared in Examples 1-8 and Comparative Examples 1-4 at current densities of 0.1C, 1C, 2C, and 5C, as well as the capacity retention after 100 cycles at room temperature and 100 cycles at high temperature using 1C.
[0155] Table 1. Tap density and compacted density of manganese trioxide synthesized in the examples and comparative examples, and the corresponding tap density and compacted density of lithium manganate synthesized in the examples.
[0156] Table 2. Rate performance and cycle performance of lithium manganese oxide synthesized in the examples and comparative examples.
[0157] analyze: As can be seen from the accompanying drawings and performance test data, this invention successfully constructed a high-density polycrystalline manganese trioxide structure through a "pore-filling-in-situ composite" strategy. Figure 2 The XRD pattern of the intermediate confirms that the intermediate is a composite phase of Mn2O3 and Mn3O4, and the first calcination achieved the expected crystal phase regulation. Figure 3 The SEM image of the intermediate surface clearly shows uniformly distributed nanoscale pores, proving that the polymer microsphere pore-forming strategy is effective and provides sufficient space for subsequent filling. Figure 4 The XRD pattern of the final product shows that the product has complete peak shape, no impurities, and high crystallinity, confirming that it has been completely transformed into pure polycrystalline manganese trioxide after the second calcination. Figure 5 The SEM image of the final product shows that the original pores of the intermediate are fully filled, the particles are tightly bound together with no obvious gaps, and the microstructure is highly compacted.
[0158] The results in Tables 1 and 2 clearly show that, compared with the materials prepared in Comparative Examples 1 to 4, the manganese oxide materials obtained in Examples 1 to 8 have a significant advantage in tap density. The prepared lithium manganese oxide batteries also show significant improvements in tap density, compaction density, rate performance, and cycle performance.
[0159] Batteries prepared from lithium manganese oxide materials obtained in Comparative Examples 1-4 exhibited low discharge capacity, as well as poor tap density and compaction density of the material powder. This is primarily because Comparative Example 1 lacked polymer microsphere pore-forming, preventing nano-manganese dioxide from filling the particle interior and forcing it to adhere to the surface or form independent aggregates. Comparative Example 2 lacked manganese dioxide filling and secondary calcination, resulting in numerous voids within the precursor and a low expected tap density. In Comparative Example 3, the manganese dioxide filler particle size was much larger than the framework pore size, preventing it from entering the pores and achieving densification. Comparative Example 4 lacked organic acid gelation and in-situ reaction, instead directly dry-mixing porous polycrystalline manganese oxide with nano-manganese dioxide, resulting in poor filling uniformity and weak interfacial bonding. These factors directly affected the final tap density, compaction density, and electrochemical performance of the lithium manganese oxide material.
[0160] Examples 1-8 strictly followed the key technical solutions of this invention. First, a porous manganese oxide framework was constructed by decomposing polymer microspheres during the first calcination, providing space for subsequent densification. Second, small-particle manganese dioxide was uniformly fixed in the pores of the framework through the complexation and gelation effects of organic acids, forming a stable network structure. Finally, an in-situ solid-phase reaction was initiated by the second calcination, causing manganese dioxide to release oxygen and transform into manganese trioxide, while simultaneously oxidizing the residual manganese tetroxide in the framework, achieving chemical bonding and crystal phase unification of multiple components. Through the dual effects of physical filling and chemical reaction, the internal voids of the particles were significantly eliminated, constructing a dense, continuous three-dimensional interpenetrating structure, thereby greatly improving the tap density of the material and obtaining high-purity, high-quality polycrystalline manganese trioxide with a uniform microstructure. Therefore, the final lithium manganese oxide material possesses both high tap density, high compaction density, and excellent rate performance and cycling performance.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing high-tap-density polycrystalline manganese trioxide, characterized in that, include: Manganese tetroxide is mixed with polymer microspheres and subjected to a first calcination treatment to obtain porous polycrystalline manganese oxide; wherein, the manganese oxide includes a composite of manganese trioxide and manganese tetroxide; The porous polycrystalline manganese oxide and manganese dioxide are mixed with an aqueous organic acid solution and then gelled to obtain a gel product. The gel product is then subjected to a second calcination treatment to obtain the high tap density polycrystalline manganese trioxide. The D50 particle size of the manganese tetroxide is 7 micrometers to 12 micrometers; The D50 particle size of the polymer microspheres is 100 nm to 200 nm. The D50 particle size of the manganese dioxide is 100 nm to 200 nm. The polymer microspheres include at least one of polystyrene microspheres and polymethyl methacrylate microspheres; The mass of the polymer microspheres is 5% to 20% of the total mass of the manganese tetroxide.
2. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The temperature of the first calcination treatment is 400℃~600℃.
3. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The first calcination treatment takes 2 to 12 hours.
4. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The temperature of the second calcination treatment is 600℃~800℃.
5. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The second calcination treatment takes 2 to 12 hours.
6. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The organic acid includes at least one of citric acid, oxalic acid, and tartaric acid.
7. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The gelation process includes heating the mixture under stirring until a gel is formed.
8. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The step of mixing manganese tetroxide with polymer microspheres also includes adding a metal dopant; wherein the mass of the metal element in the metal dopant is 0.1% to 2% of the total mass of the manganese tetroxide.
9. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The mass ratio of the porous polycrystalline manganese oxide to manganese dioxide is (6-8):(4-2).
10. The method for preparing high-tap-density polycrystalline manganese trioxide as described in claim 1, characterized in that, The porous polycrystalline manganese oxide has a porosity of 20% to 40%, and the proportion of manganese trioxide phase is greater than 60%.
11. The method for preparing high tap density polycrystalline manganese trioxide as described in claim 1, characterized in that, The high-tap-density polycrystalline manganese trioxide has a tap density greater than 2.5 g / cm³. 3 .
12. A high-tap-density polycrystalline manganese trioxide, characterized in that, It was prepared by the method for preparing high tap density polycrystalline manganese trioxide as described in any one of claims 1-11; The high-tap-density polycrystalline manganese trioxide has a tap density greater than 2.5 g / cm³. 3 .
13. A lithium manganese oxide cathode material, characterized in that, It is prepared by reacting the high tap density polycrystalline manganese trioxide as described in claim 12 with a lithium source.
14. The lithium manganese oxide cathode material as described in claim 13, characterized in that, The discharge capacity of the lithium manganese oxide cathode material is greater than 120 mAh / g.
15. A method for preparing a lithium manganese oxide cathode material, characterized in that, include: The high tap density polycrystalline manganese trioxide as described in claim 12 is mixed with a lithium source and subjected to a third calcination treatment at a temperature of 600℃ to 800℃ to prepare a lithium manganese oxide cathode material.
16. A battery, characterized in that, Includes the lithium manganese oxide cathode material as described in claim 13 or 14; or, the lithium manganese oxide cathode material prepared by the preparation method described in claim 15.
17. An electrical-related device, characterized in that, Includes the battery as described in claim 16.
Citation Information
Patent Citations
Preparation method of battery-grade manganese sesquioxide and product of battery-grade manganese sesquioxide
CN115959710A